Thermally crosslinked poly(glucuronic acid)-chitosan films with high oxygen and water vapor barrier properties

Thermally crosslinked chitosan-poly(glucuronic acid) films address the challenge of achieving both oxygen and water vapor barrier properties in packaging, offering sustainable and recyclable alternatives with performance comparable to traditional plastics.

JP7616696B2Active Publication Date: 2025-01-17GEORGIA TECH RES CORP
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2022544631
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-09-30
Filing Date
2020-09-30
Publication Date
2025-01-17
Estimated Expiration
2040-09-30

AI Technical Summary

Technical Problem

Conventional packaging materials derived from renewable resources face challenges in achieving both low oxygen and water vapor transmission rates while maintaining mechanical properties, often being brittle and difficult to recycle due to multiple layered structures that are hard to separate.

Method used

Thermally crosslinked films composed of chitosan-poly(glucuronic acid) and optionally poly(alkylene glycol) are developed, utilizing the reaction between amine groups of chitosan and acid groups of poly(glucuronic acid to form a crosslinked network, enhancing barrier properties and dimensional variability.

Benefits of technology

The films exhibit low oxygen permeability and good water vapor permeability, making them suitable for sustainable packaging applications with improved recyclability and compostability, comparable to traditional plastics in performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007616696000003
    Figure 0007616696000003
  • Figure 0007616696000004
    Figure 0007616696000004
  • Figure 0007616696000001
    Figure 0007616696000001
Patent Text Reader

Abstract

Films and materials are disclosed that include poly(alkylene glycol)-chitosan and / or chitin-poly(glucuronic acid), and chitosan and / or chitin-poly(glucuronic acid). Methods of making such films are disclosed, particularly involving thermal crosslinking of poly(glucuronic acid) with chitosan.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] CROSS-REFERENCE TO RELATED APPLICATIONS This application claims the benefit of U.S. Provisional Application No. 62 / 908,009, filed September 30, 2019, which is incorporated by reference in its entirety. [Background technology]

[0002] Currently, there is a great deal of interest in producing packaging plastics from renewable resources. In particular, flexible plastics used to protect food from oxygen and water are generally not produced from renewable resources and are difficult to recycle. In order to achieve acceptably low oxygen and water vapor transmission rates and suitable mechanical properties, in conventional packaging, many layers are produced together. These layers are difficult to separate and recycle after use. By deriving the layers from biomass-derived materials, flexible films that are compostable or recyclable can be achieved. Cellulose and chitin are the first and second most abundant poly(saccharides) occurring in nature, each of which is biodegradable and compostable through various means. Cellulose and chitin-based films with oxygen permeability properties suitable for food packaging have been investigated, but in general, they suffer from high water absorption rates that adversely affect oxygen barrier properties. In addition, many of the materials are unacceptably brittle and difficult to manufacture to be dimensionally reconfigurable. Thus, there is interest in developing plastic films suitable for food packaging that are derived from cellulose or chitin, or other poly(saccharides) found in nature or agriculture, but that combine oxygen and water vapor barrier properties and can be manufactured to be dimensionally adaptable. The compositions and methods disclosed herein address these and other needs. Summary of the Invention

[0003] In accordance with the purpose of the disclosed materials and methods as embodied and broadly described herein, the disclosed subject matter in one aspect relates to compounds, compositions, and methods of making and using the compounds and compositions. In particular aspects, the disclosed subject matter relates to films and materials comprising poly(alkylene glycol)-chitosan-poly(glucuronic acid) and chitosan-poly(glucuronic acid). Disclosed herein is a method of making such films, in particular involving thermal crosslinking of poly(glucuronic acid) with chitosan.

[0004] Additional advantages will be set forth in part in the description which follows, and in part will be obvious from the description, or may be learned by practice of the aspects described hereinafter. The advantages described below will be realized and attained by means of the elements and combinations particularly pointed out in the appended claims. It is to be understood that both the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive. [Brief description of the drawings]

[0005] The accompanying drawings, which are incorporated in and constitute a part of this specification, illustrate several aspects described below.

[0006] [Figure 1] 1 is a graph of the water vapor permeability of various films disclosed herein, showing the positive effect of adding heat treatment on lowering WVTR. [Diagram 2] FTIR spectra of four samples are included: Ch-PG film before (Ch-PG) and after (Ch-PG(HT)) heat treatment, and PEG-Ch-PG film before (PEG-Ch-PG) and after (PEG-Ch-PG(HT)) heat treatment. The effect of heat treatment (HT) on the appearance of additional amide bonds is shown. (Chitosan already has some amide bonds present.) DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] The materials, compounds, compositions, and methods described herein may be more readily understood by reference to the following detailed description of certain aspects of the disclosed subject matter and the examples included therein.

[0008] Before the present materials, compounds, compositions, and methods are disclosed and described, it is to be understood that the embodiments described below are not limited to particular synthetic methods or to particular reagents, as such may, of course, vary. It is also to be understood that the terminology used herein is for the purpose of describing particular embodiments only, and is not intended to be limiting.

[0009] Also, throughout this specification, various publications are referenced. The disclosures of these publications in their entireties are hereby incorporated by reference into this application in order to more fully describe the state of the art to which the disclosed subject matter pertains. The references disclosed are also individually and specifically incorporated by reference herein for the material contained in them that is discussed in the sentence in which the reference is relied upon.

[0010] General definition In this specification and the claims that follow, reference will be made to a number of terms that shall be defined to have the following meanings.

[0011] Throughout the specification and claims, the word "comprise" and other forms of the word, such as "comprising" and "comprises," are intended to mean, for example, without limitation, other additives, ingredients, or steps and are not intended to exclude them.

[0012] As used in the description and the appended claims, the singular forms "a," "an," and "the" include plural referents unless the context clearly dictates otherwise. Thus, for example, reference to a "composition" includes mixtures of two or more such compositions, reference to an "inhibitor" includes mixtures of two or more such inhibitors, and so forth.

[0013] "Optional" or "optionally" means that a subsequently described event or circumstance may or may not occur, and the description includes cases where the event or circumstance occurs and cases where it does not occur.

[0014] Notwithstanding that the numerical ranges and parameters setting forth the broad scope of the present disclosure are approximations, the numerical values ​​set forth in the specific examples are reported as precisely as possible. However, any numerical value inherently contains certain errors necessarily resulting from the standard deviation found in their respective testing measurements. Moreover, when numerical ranges of various scopes are set forth herein, it is contemplated that any combination of these values, including the recited values, may be used. Furthermore, as used herein, ranges can be expressed from one particular value with the use of "about" and / or to another particular value with the use of "about." When such a range is expressed, another embodiment includes from one particular value and / or to the other particular value. Similarly, when values ​​are expressed as approximations by use of the antecedent "about," it will be understood that the particular value constitutes another aspect. Moreover, it will be understood that each endpoint of a range is significant both in relation to the other endpoint and independently of the other endpoint. Unless otherwise stated, the term "about" means within 5% (e.g., within 2% or 1%) of the particular value modified by the term "about."

[0015] It should be understood that throughout this specification, the identifiers "first" and "second" are used solely to aid in distinguishing between various components and steps of the disclosed subject matter. The identifiers "first" and "second" are not intended to imply any particular order, quantity, preference, or importance to the components or steps modified by these terms.

[0016] As used herein, the term "composition" is intended to encompass a product containing the specified ingredients in the specified amounts, as well as any product resulting directly or indirectly from combining the specified ingredients in the specified amounts.

[0017] References in this specification and the concluding claims to parts by weight of a particular element or component in a composition indicate the weight relationship between the element or component and any other elements or components in the composition or article to which the parts by weight are expressed. Thus, in a mixture containing 2 parts by weight of component X and 5 parts by weight of component Y, X and Y are present in a weight ratio of 2:5, and are present in such ratio regardless of whether additional components are included in the mixture.

[0018] Weight percentages (wt %) of components are based on the total weight of the formulation or composition in which the component is included, unless specifically stated to the contrary.

[0019] Reference will now be made in detail to certain embodiments of the disclosed materials, compounds, compositions, articles and methods, examples of which are illustrated in the accompanying examples and figures.

[0020] Compositions and methods Disclosed herein are chitosan-poly(glucuronic acid) films or membranes with or without the presence of poly(alkylene glycol) or similar poly(alkylene oxide) polymers (e.g., poly(ethylene glycol) (PEG)). The amine and acid groups on the chitosan and poly(glucuronic acid) react to form a crosslinked network polymer. The crosslinked network likely can accelerate solidification during manufacturing (through precipitation of high molecular mass products) and limit swelling of the material by water vapor during use. The disclosed materials can have low oxygen transmission rates and good water vapor transmission rates, and thus can be used for barrier applications in packaging. These materials can be used in sustainably derived food, beverage, and pharmaceutical packaging.

[0021] Poly(glucuronic acid) Poly(glucuronic acid)s are homopolymers of glucuronic acid. They can be found in nature or produced synthetically by regioselective oxidation of natural glucans such as cellulose. Isogai et al. produced water-soluble β-(1,4)-D-poly(glucuronic acid) (called cellouronic acid) by regioselective oxidation of the C6 primary hydroxyls of regenerated cellulose using 2,2,6,6-tetramethylpiperidine-1-oxyl radical (TEMPO) (Isogai, A., et al., Preparation of Polyuronic Acid from Cellulose by TEMPO-mediated Oxidation. Cellulose, 1998, 5(3):153-164). Several sources of natural water-soluble β-(1,4)-D-poly(glucuronic acid) have also been identified, one of which is the exopolysaccharide excreted by alfalfa rhizobia.

[0022] The amount of poly(glucuronic acid) in the disclosed compositions can be at least about 5% by weight, e.g., at least about 10% by weight, about 15% by weight, about 20% by weight, about 25% by weight, about 30% by weight, about 35% by weight, about 40% by weight, about 45% by weight, about 50% by weight, about 55% by weight, about 60% by weight, about 65% by weight, about 70% by weight, about 75% by weight, about 80% by weight, about 85% by weight, about 90% by weight, or about 95% by weight. In other examples, the amount of poly(glucuronic acid) in the disclosed compositions can be less than about 95% by weight, e.g., about 90% by weight, about 85% by weight, about 80% by weight, about 75% by weight, about 70% by weight, about 65% by weight, about 60% by weight, about 55% by weight, about 50% by weight, about 45% by weight, about 40% by weight, about 35% by weight, about 30% by weight, about 25% by weight, about 20% by weight, about 15% by weight, about 10% by weight, or less than about 5% by weight. In still other examples, the amount of poly(glucuronic acid) in the disclosed compositions can be about 5%, about 10%, about 15%, about 20%, about 25%, about 30%, about 35%, about 40%, about 45%, about 50%, about 55%, about 60%, about 65%, about 70%, about 75%, about 80%, about 85%, about 90%, or about 95% by weight, any of the recited values ​​may represent the upper or lower endpoints of a range. For example, the amount of poly(glucuronic acid) in the disclosed compositions can be about 5% to about 95% by weight, about 25% to about 75% by weight, about 30% to about 50% by weight, or about 50% to about 70% by weight. In specific examples, the amount of poly(glucuronic acid) in the disclosed compositions can be about 33% or about 50% by weight.

[0023] Chitosan Chitosan is derived from chitin, another abundantly available biopolymer whose natural abundance is in the same order of magnitude as cellulose (Barikani, M., et al., Preparation and application of chitin and its derivatives: a review. Iranian Polymer J., 2014, 23(4): 307-326). Chitosan is a linear polysaccharide and homopolymer of D-glucosamine, produced by the deacetylation of chitin (Hamed, I., et al., Industrial applications of crustacean by-products (chitin, chitosan, and chitooligosaccharides): A review. Trends Food Sci. Tech., 2016, 48: 40-50). Due to the presence of secondary amino groups, chitosan is soluble in dilute acids such as acetic acid, formic acid, succinic acid, etc. Chitin and chitosan can be considered the same material, but with different degrees of deacetylation and correspondingly different contents of secondary (-NH2) amine groups. Chitosan is chitin with a degree of acetylation of less than 50 mole %. Naturally occurring chitin contains some fragments of chitosan distributed as comonomers along the chain, and the process of extracting chitin from its parent source (such as the exoskeleton of crustaceans) leads to some deacetylation, which can be carried to an extreme to produce chitosan. Chitosan is soluble in dilute aqueous acidic solutions, while chitin is insoluble and remains in solid fibrous form. The solid fibers exist as large aggregates or can be reduced to nanocrystals or nanofibers through processing such as homogenization. Although the primary examples provided herein are with chitosan, the principles of the invention are applicable to other forms of chitin, including nanofibers and nanocrystals that contain some amount of secondary amines on their surface. Thus, it is expressly contemplated that the disclosed methods and compositions can substitute chitosan for chitin.

[0024] The amount of chitosan in the disclosed compositions can be at least about 5% by weight, e.g., at least about 10% by weight, about 15% by weight, about 20% by weight, about 25% by weight, about 30% by weight, about 35% by weight, about 40% by weight, about 45% by weight, about 50% by weight, about 55% by weight, about 60% by weight, about 65% by weight, about 70% by weight, about 75% by weight, about 80% by weight, about 85% by weight, about 90% by weight, or about 95% by weight. In other examples, the amount of chitosan in the disclosed compositions can be less than about 95% by weight, e.g., about 90% by weight, about 85% by weight, about 80% by weight, about 75% by weight, about 70% by weight, about 65% by weight, about 60% by weight, about 55% by weight, about 50% by weight, about 45% by weight, about 40% by weight, about 35% by weight, about 30% by weight, about 25% by weight, about 20% by weight, about 15% by weight, about 10% by weight, or less than about 5% by weight. In still other examples, the amount of chitosan in the disclosed compositions can be about 5% by weight, about 10% by weight, about 15% by weight, about 20% by weight, about 25% by weight, about 30% by weight, about 35% by weight, about 40% by weight, about 45% by weight, about 50% by weight, about 55% by weight, about 60% by weight, about 65% by weight, about 70% by weight, about 75% by weight, about 80% by weight, about 85% by weight, about 90% by weight, or about 95% by weight, any of the recited values ​​may constitute the upper or lower endpoints of a range. For example, the amount of chitosan in the disclosed compositions can be about 5% by weight to about 95% by weight, about 25% by weight to about 75% by weight, about 30% by weight to about 50% by weight, or about 50% by weight to about 70% by weight. In specific examples, the amount of chitosan in the disclosed compositions can be about 33% by weight or about 50% by weight.

[0025] Poly(alkylene glycol) The disclosed compositions can contain poly(alkylene glycol) or similar poly(alkylene oxide) polymers. Examples of such polymers include, but are not limited to, poly(ethylene glycol) and poly(propylene glycol). When present, the poly(alkylene glycol) or similar poly(alkylene oxide) polymer, such as poly(ethylene glycol), can have a molecular weight of 1,000 to about 10,000 g / mol, e.g., about 2,000 g / mol to about 8,000 g / mol, about 4,000 g / mol to about 6,000 g / mol, about 1,000 g / mol to about 7,000 g / mol, or about 3,000 g / mol to 5,000 g / mol. The amount of poly(alkylene glycol) or similar poly(alkylene oxide) polymer in the disclosed compositions can be about 0.1% to about 40% by weight, e.g., about 0.5%, about 1%, about 5%, about 10%, about 15%, about 20%, about 25%, about 30%, about 35%, or about 40% by weight, with any of the recited values ​​forming the upper or lower end of the range. In further examples, the amount of poly(alkylene glycol) or similar poly(alkylene oxide) polymer can be about 0.1% to about 35% by weight, about 5% to about 30% by weight, about 10% to about 25% by weight, about 15% to about 40% by weight, about 20% to about 35% by weight, or about 33% by weight. In other examples, the compositions do not contain poly(alkylene glycol) or similar poly(alkylene oxide) polymer.

[0026] Crosslinking In the disclosed compositions, chitosan is crosslinked with poly(glucuronic acid). There are several methods for crosslinking chitosan. Chitosan itself (Harish Prashanth, KV, et al., Tharanathan, Crosslinked chitosan-preparation and characterization. Carbohydrate Res., 2006, 341(1):169-173), or other reagents such as o-phthaldialdehyde (Rinaudo, M., New way to crosslink chitosan in aqueous solution. Eur. Polymer J., 2010, 46(7):1537-1544), glutaraldehyde (Monteiro, OAC, et al., Some studies of crosslinking chitosan-glutaraldehyde interaction in a homogeneous system. Intl. J. Biol. Macromol., 1999, 26(2):119-128), vanillin (Zou, Q., et al., Preparation and characterization of vanillin-crosslinked chitosan therapeutic bioactive microcarriers. Intl. J. Biol. Macromol., 2015, 79: 736-747), and crosslinking of chitosan with many others has already been studied. Similarly, cellulose and chitosan have been used to produce antibacterial composites (Yang, J., et al., Cellulose-Chitosan Antibacterial Composite Films Prepared from LiBr Solution. Polymers, 2018, 10(10): 1058), and blends of these two polymers have been studied by Isogai (Isogai, A., et al., Preparation of cellulose-chitosan polymer blends. Carbohydrate Polymers, 1992, 19(1): 25-28).Alam and Christopher produced cross-linked cellulose-chitosan superabsorbent hydrogels by cross-linking partially oxidized cellulose aldehyde with carboxymethylated chitosan (Alam, MN, et al., Natural Cellulose-Chitosan Cross-Linked Superabsorbent Hydrogels with Superior Swelling Properties. ACS Sustainable Chem. Eng., 2018, 6(7):8736-8742).

[0027] Tang et al. were able to couple chitosan and TEMPO-oxidized nanofibrilliated cellulose by utilizing the electrostatic attraction between them at room temperature and then heating to generate covalent amide linkages (Tang, R., et al., Coupling chitosan and TEMPO-oxidized nanofibrilliated cellulose by electrostatic attraction and chemical reaction. Carbohydrate Polymers, 2018, 202: 84-90). Notably, the cellulose used by Tang et al. was a solid nanofiber of cellulose whose surface was lightly oxidized to modify only the surface with acid groups. Soni et al. used TEMPO-oxidized cellulose nanofibers and chitosan to generate transparent gas barrier films. They found that the films had better oxygen gas barrier properties than chitosan films and better thermal and mechanical stability than chitosan films (Soni, B., et al., Transparent bionanocomposite films based on chitosan and TEMPO-oxidized cellulose nanofibers with enhanced mechanical and barrier properties. Carbohydrate Polymers, 2016, 151: 779-789). Choo et al. produced polyvinyl alcohol-chitosan composite films and reinforced them with TEMPO-oxidized cellulose nanofibers (Choo, K., et al., Preparation and Characterization of Polyvinyl Alcohol-Chitosan Composite Films Reinforced with Cellulose Nanofiber. Materials, 2016, 9(8): 644).Yan et al. prepared a polyelectrolyte complex by utilizing negatively charged carboxylic curdlan (Cc) with a β-1,3-poly(glucuronic acid) structure and positively charged chitosan (Yan, J.-K., et al., Formation and characterization of polyelectrolyte complex synthesized by chitosan and carboxylic curdlan for 5-fluorouracil delivery. Intl. J. Biol. Macromol., 2018, 107: 397-405).

[0028] Sannino et al. (U.S. Pat. No. 8,658,147) describe a method for preparing polymer hydrogels using polycarboxylic acids, including poly(glucuronic acid), as crosslinkers. Valentova (U.S. Publication No. 2010-0260809) describes chitosan-glucan complexes for wound healing applications. Buchanan et al. (U.S. Pat. No. 8,816,066) describe a method for the oxidation of cellulose ester interpolymers using TEMPO, which can also be applied to chitosan. They also describe the complexation between oppositely charged macromolecules using anionic cellulose ester interpolymers and chitosan for therapeutic agent solubility modifiers.

[0029] As disclosed herein, the cross-linking reaction is between chitosan and poly(glucuronic acid) and is thermally initiated.

[0030] Examples Specific examples of the compositions disclosed herein are provided in Table 1. [Table 1]

[0031] method Disclosed herein are methods for making the disclosed poly(alkylene glycol)-chitosan-poly(glucuronic acid) and chitosan-poly(glucuronic acid). In one aspect, disclosed herein is a method for making a poly(alkylene glycol)-chitosan-poly(glucuronic acid) film, comprising contacting cellulose with NaOH and a poly(alkylene glycol), such as poly(ethylene glycol), to form a solution comprising poly(alkylene glycol), NaOH, and cellulose; contacting the solution comprising poly(alkylene glycol), NaOH, and cellulose with 2,2,6,6-tetramethylpiperidine-1-oxyl radical and an oxidizing agent to form a solution comprising poly(glucuronic acid) and poly(alkylene glycol); The method includes separating radicals, oxidizing agents, and cellulose from a solution containing poly(glucuronic acid) and poly(alkylene glycol), contacting the solution containing poly(glucuronic acid) and poly(alkylene glycol) with an acidic solution of chitosan to form a solution containing chitosan, poly(glucuronic acid), and poly(alkylene glycol), casting the solution containing chitosan, poly(glucuronic acid), and poly(alkylene glycol) into a film, and heating the film to crosslink the poly(glucuronic acid) with the chitosan to obtain a poly(alkylene glycol)-chitosan-poly(glucuronic acid) film. In certain embodiments, the cellulose and chitosan components are completely soluble when they undergo heat treatment and amide reaction.

[0032] In another aspect, provided herein is a method of making a chitosan-poly(glucuronic acid) film, comprising contacting cellulose with NaOH and a poly(alkylene glycol), e.g., poly(ethylene glycol), to form a solution comprising poly(alkylene glycol) and cellulose; contacting the solution comprising poly(alkylene glycol) and cellulose with 2,2,6,6-tetramethylpiperidine-1-oxyl radical and an oxidizing agent to form a solution comprising poly(glucuronic acid) and poly(alkylene glycol); and forming a chitosan-poly(glucuronic acid) film from the solution comprising poly(glucuronic acid). A method is disclosed that includes isolating poly(glucuronic acid) from poly(alkylene glycol), 2,2,6,6-tetramethylpiperidine-1-oxyl radical, an oxidant, cellulose, and poly(alkylene glycol); contacting the poly(glucuronic acid) with an acidic solution of chitosan to form a solution comprising chitosan and poly(glucuronic acid); casting the solution comprising chitosan and poly(glucuronic acid) into a film; and heating the film to crosslink the poly(glucuronic acid) with the chitosan to obtain a chitosan-poly(glucuronic acid) film.

[0033] Contacting cellulose with NaOH and poly(alkylene glycol) to form a solution containing poly(alkylene glycol) and cellulose can be carried out as disclosed by Yan and Gao, who describe dissolving cellulose in a 1 wt% poly(ethylene glycol) (PEG) / 9 wt% NaOH solution (Yan, L., et al., Dissolving of cellulose in PEG / NaOH aqueous solution. Cellulose, 2008, 15(6):789, incorporated herein by reference in its entirety for its teachings on dissolving cellulose). They were able to produce a cellulose solution of 1-11.5 wt% cellulose by mixing cellulose in a PEG / NaOH solution, freezing the mixture at -15°C for 12 hours, and then thawing the mixture under vigorous agitation to produce a homogenous cellulose solution. As used herein, dissolving cellulose using NaOH and poly(alkylene glycol) can be carried out with any cellulose source. For example, the cellulose can be microcrystalline cellulose, nanocrystalline cellulose, cellulosic biomass, such as cotton, wood pulp, hemp, or linters. NaOH can be provided as a solution to which the poly(alkylene glycol) is added, or can be added to a solution of the poly(alkylene glycol). Alternatively, the cellulose can be added to the poly(alkylene glycol) with NaOH or to which NaOH is then added. Still further, the poly(alkylene glycol) can be added to the cellulose with NaOH or to which NaOH is then added. The poly(alkylene glycol) can have an average MW of about 1,000 g / mol to about 10,000 g / mol, for example, about 2,000 g / mol to about 8,000 g / mol, about 4,000 g / mol to about 6,000 g / mol, about 1,000 g / mol to about 7,000 g / mol, or about 3,000 g / mol to about 5,000 g / mol. In one particular example, the solution is frozen, for example with liquid nitrogen, and then thawed with stirring to obtain a clear cellulose solution with poly(alkylene glycol).The resulting solution may contain about 1% to about 12% by weight of the solution, e.g., about 1% to about 11% by weight, about 1% to about 10% by weight, about 1% to about 9% by weight, about 1% to about 8% by weight, about 1% to about 7% by weight, about 1% to about 6% by weight, about 5% to about 12% by weight, about 5% to about 11% by weight, about 5% to about 10% by weight, or about 10% to about 12% by weight of the solution.

[0034] Without wishing to be bound by theory, it is believed that starting with NaCNC leads to easier processing because the CNC has already been chemically processed and the sulfonic acid groups are easily removed to form carboxylic acid groups in the poly(glucuronic acid) product. However, it may be cheaper to start with pulp to avoid the processing used to isolate NaCNC.

[0035] A solution containing poly(alkylene glycol) and cellulose can be contacted with 2,2,6,6-tetramethylpiperidine-1-oxyl (TEMPO) radical and an oxidizing agent to form a solution containing poly(glucuronic acid) and poly(alkylene glycol). As alternatives to TEMPO, 2,2,5,5-tetramethylpyrroline-N-oxyl and 4,4-dimethyloxazolidine-N-oxyl can be used. The oxidizing agent can include sodium hypochlorite, nitrogen dioxide and periodate, metaperiodate and dichromate, or dichromate in oxalic acid. Additional water-soluble alkali salts can also be included: water-soluble salts of sodium or potassium, such as sodium bromide, sodium chloride, potassium bromide, potassium chloride, or sodium hydroxide. Tang et al. describe the production of water-soluble TEMPO-oxidized cellulose by dissolving cellulose in a urea / NaOH solution (Tang, Z., et al., TEMPO-Oxidized Cellulose with High Degree of Oxidation. Polymers, 2017, 9(9):421). Cellulose was mixed in a 7:12:81 NaOH:urea:water solution at -12°C under vigorous stirring. The solution was centrifuged at 8000 rpm for 15 min to remove insoluble impurities, and the solution was diluted with 40 L of water. The suspension was then filtered and washed with deionized water until the pH approached neutral. The suspension was then cooled in liquid nitrogen for 30 min and lyophilized at -50°C for 3 days to give NaOH / urea treated cellulose oxidized utilizing TEMPO-sodium bromide-sodium hypochlorite to yield water-soluble poly(glucuronic acid). Unlike the process of Tang et al., the cellulose solution herein contains poly(alkylene glycol) and NaOH.

[0036] The 2,2,6,6-tetramethylpiperidine-1-oxyl radical, oxidizing agent, and cellulose can be separated from the solution containing poly(glucuronic acid) and poly(alkylene glycol) or similar poly(alkylene oxide) polymers. This can be accomplished by centrifuging or dialysis of the solution against water. The dialysis step can be performed multiple times. In some embodiments, poly(glucuronic acid) can be separated from poly(alkylene glycol) or similar poly(alkylene oxide) polymers by precipitating and then isolating the poly(glucuronic acid). Precipitation can be induced by adding a precipitating reagent such as ethanol or propanol.

[0037] The solution containing poly(glucuronic acid) and (optionally) poly(alkylene glycol) or similar poly(alkylene oxide) polymer can then be contacted with an acidic solution of chitosan to form a solution containing chitosan, poly(glucuronic acid), and (optionally) poly(alkylene glycol) or similar poly(alkylene oxide) polymer. The acidic solution of chitosan can have a pH of 2 to 4, e.g., 2.5 to 3.5, or 3.

[0038] The solution containing chitosan, poly(glucuronic acid), and (optionally) poly(alkylene glycol) or similar poly(alkylene oxide) polymer can then be cast into a film. Casting can be performed by pouring the solution into a mold, onto a substrate, rolling the solution onto the substrate, spray coating onto the substrate, dip coating onto the substrate, or by continuous coating including doctor blade, knife edge, slot die, flexographic, or gravure coating methods. The resulting wet film is then dried at elevated temperatures. The result is then dried.

[0039] The final step is to heat the film to crosslink the poly(glucuronic acid) with the chitosan, resulting in a chitosan-poly(glucuronic acid) film, with or without poly(alkylene glycol) or similar poly(alkylene oxide) polymer. Heating can be carried out at temperatures between 35 and 250°C, e.g., 50-225°C, 70-200°C, 90-175°C, 110-150°C, 75-250°C, 100-200°C, 35-100°C, or 150-250°C.

[0040] The resulting compositions can then be used to form films, wrappers, packaging materials, packaging films, bandages, garments, and other useful articles. EXAMPLES

[0041] The following examples are presented below to illustrate methods and results according to the disclosed subject matter. These examples are not intended to be inclusive of all aspects of the subject matter disclosed herein, but rather to illustrate representative methods and results. These examples are not intended to exclude equivalents and variations of the present invention that are obvious to those skilled in the art.

[0042] ACS grade sodium hydroxide pellets and ACS grade crystalline sodium bromide were obtained from VWR (Radnor, PA). Solid poly(ethylene glycol) 2000 was obtained from Fluka Biochemika (Steinheim, Germany). TEMPO free radical was obtained from Alfa Aesar (Ward Hill, MA). Deionized (DI) water was obtained from a Thermo scientific GenPure UV / UF xCAD plus water purification system. Lyophilized cellulose nanocrystals (CNC) were obtained from Forest Products lab (Madison, WI). Glacial acetic acid was purchased from Sigma Aldrich (St. Louis, MO). Chitosan powder (minimum 90% deacetylated) was obtained from Spectrum Chemicals (Gardena, CA). Sodium hypochlorite was obtained as a 6% solution from Publix (Lakeland, FL).

[0043] Example 1: PEG-chitosan-poly(glucuronic acid) film 9g NaOH pellets and 1g PEG2000 were dissolved in 90mL deionized water. 1g freeze-dried CNC was added to it. Liquid nitrogen was used to freeze the solution solid and the frozen solution was kept in a refrigerator at 0°C for 24 hours. The frozen solution was thawed under vigorous stirring to obtain a clear cellulose solution. 12.7g sodium bromide and 0.16g TEMPO were added to it. After complete dissolution, 114mL of 6% sodium hypochlorite was added to the solution over 10 minutes and the solution was allowed to react for 6 hours. The reaction was quenched with 5mL ethanol. The resulting solution was dialyzed against 500 volumes of deionized water until the pH was 7 to remove TEMPO, sodium bromide, and sodium hydroxide.

[0044] Sufficient glacial acetic acid was dissolved in water to obtain a solution with a pH of 3. Chitosan was dissolved in this pH 3 acidic water as a 1% solution. 26 mL of the dialyzed cellulose-PEG solution was mixed with 24 mL of the chitosan solution. The solution was stirred at 200 RPM for 10 minutes, and then the solution was cast in a plastic (polyethylene) boat. The film was air-dried for 14 days to obtain a free-standing film.

[0045] The PEG-chitosan-poly(glucuronic acid) film (PEG-Ch-PG) was then heated in a vacuum oven at 150°C for 3 hours to obtain a heat-treated film (PEG-Ch-PG(HT)). During the heat treatment, chitosan and glucuronic acid are expected to react to form amide bond linkages. These conditions were taken from Sharma et al. (Sharma, S., et al., Thermally enhanced high performance cellulose nano fibril barrier membranes. RSC Advances, 2014, 4(85):45136-45142).

[0046] Example 2: Chitosan-poly(glucuronic acid) film The dialyzed cellulose solution was mixed with ethanol to precipitate poly(glucuronic acid). The precipitate was isolated by centrifuging the suspension at 3000 RPM for 10 min. The precipitate was washed with ethanol and the suspension was centrifuged again under the same conditions. This procedure was repeated three times to obtain pure poly(glucuronic acid). Poly(glucuronic acid) was dissolved in water as a 1 wt% solution. 26 mL of this solution was mixed with 24 mL of the chitosan solution described above. The resulting poly(glucuronic acid) and chitosan solution was then solution cast as described above to obtain a free-standing film.

[0047] The chitosan-poly(glucuronic acid) (Ch-PG) film was then heated in a vacuum oven at 150 °C for 3 h to obtain a heat-treated film (Ch-PG(HT)). As shown above, during heat treatment, chitosan and glucuronic acid are expected to react to form amide bond linkages. These conditions were taken from Sharma et al. (Sharma, S., et al., Thermally enhanced high performance cellulose nano fibril barrier membranes. RSC Advances, 2014, 4(85):45136-45142).

[0048] Example 3: Permeability Assay The oxygen gas permeability of the free-standing films was measured using a MOCON OXTRAN instrument MOCON OXTRAN1 / 50 at 50% relative humidity (RH) and 23°C, while the water vapor permeability of the free-standing films was obtained using a MOCON PERMATRAN-W1 / 50 instrument at 30–60% RH and 23°C. The thickness of the free-standing films was measured using a micrometer.

[0049] The solid films formed by the above procedure were tested for oxygen and water vapor transmission rates. Table 2 presents the oxygen transmission rate results in permeability form normalized for thickness and oxygen pressure differential. Values ​​of 0.20 and 0.76 for PEG-Ch-PG(HT) and Ch-PG(HT), respectively, are commercially relevant and comparable to conventional barrier packaging films such as poly(ethylene terephthalate), poly(vinylidene chloride), and poly(ethylene-co-vinyl alcohol). A 1 mil (25 mm) thick film of PEG-Ch-PG(HT) at an oxygen pressure differential of 100 kPa typically provides better transmission than high barrier materials (1 cm) at 23°C and 50% relative humidity. 3 / m 2 / day) 3 / m 2 / day oxygen permeability. [Table 2]

[0050] Figure 1 presents the water vapor transmission rate (WVTR) normalized to film thickness. Up to 50% RH, Ch-PG(HT) films have a WVTR of 3–5 g mm / m 2 / day, which is similar to PET plastic. The Ch-PG(HT) film has a significantly lower WVTR at higher humidity than the untreated Ch-PH film. The PEG-Ch-PG(HT) material has a similar WVTR at humidity below 40% RH, but performance is compromised (higher WVTR) than Ch-PH as RH increases.

[0051] Example 4: Fourier transform infrared spectroscopy (FTIR). Figure 2 shows the FTIR spectra acquired for four samples. These are Ch-PG films before (Ch-PG) and after (Ch-PG(HT)) heat treatment (HT), and PEG-Ch-PG films before (PEG-Ch-PG) and after (PEG-Ch-PG(HT)) heat treatment. For the heat-treated PEG-Ch-PG(HT) film, the FTIR spectrum was recorded at 1150 cm to allow for quantitative comparison between the spectra. -1 The hydroxyl peak for the PEG-Ch-PG(HT) film was normalized using the C-O-C bridge vibration at 3450 cm, which corresponds to a weaker hydrogen bond, indicating a larger proportion of hydrogen-bonded –OH compared to the non-thermally treated PEG-Ch-PG film. -1 This is accompanied by the reappearance of a small peak at 1500-1700 cm -1 The intensity of the amide-related bands at 1320 cm for amide III points to an increase in amide bond formation. -1 increases with increasing intensity of the peak at the CN stretching.

[0052] The FTIR spectrum of the Ch-PG film shows a peak at 3450 cm -1The band corresponding to the amide is located between 1500 and 1700 cm, similar to the PEG-Ch-PG film, which does not have significant free hydrogen bonds stretching at wavenumbers above 1500 cm. -1 The FTIR data for Ch-PG(HT) and Ch-PG films are normalized so that the intensities of the C-O-C bridge vibrations are the same to allow for quantitative comparison. Heat treatment of Ch-PG(HT) increases the peak intensity of the hydrogen bond hydroxyls, but the peaks associated with weaker hydrogen bonds are not as distinct as seen in heat treated PEG-Ch-PG(HT). Similarly, the amide-related peaks also increase with heat treatment in Ch-PG(HT) compared to Ch-PG, as observed for PEG-Ch-PG(HT) vs. PEG-Ch-PG.

[0053] It will be appreciated that the above-disclosed and other features and functions, or alternatives thereof, may be combined into many other different systems or applications in which various presently foreseen or unanticipated alternatives, modifications, variations, or improvements therein may be made by those skilled in the art, and are intended to be encompassed by the following claims.

Claims

1. 1. A method for making a poly(alkylene glycol)-chitosan-poly(glucuronic acid) film comprising the steps of: contacting cellulose with NaOH and a poly(alkylene glycol) to form a solution comprising poly(alkylene glycol), NaOH, and cellulose; contacting the solution comprising poly(alkylene glycol) and cellulose with 2,2,6,6-tetramethylpiperidine-1-oxyl radical and an oxidizing agent to form a solution comprising poly(glucuronic acid) and poly(alkylene glycol); separating the 2,2,6,6-tetramethylpiperidine-1-oxyl radical, the oxidizing agent, and the cellulose from said solution containing poly(glucuronic acid) and poly(alkylene glycol); contacting the solution containing poly(glucuronic acid) and poly(alkylene glycol) with an acidic solution of chitosan to form a solution containing chitosan, poly(glucuronic acid), and poly(alkylene glycol); casting or coating said solution comprising chitosan, poly(glucuronic acid), and poly(alkylene glycol) into a film; and heating the film to crosslink the poly(glucuronic acid) with the chitosan to obtain a poly(alkylene glycol)-chitosan-poly(glucuronic acid) film.

2. 1. A method for making a chitosan-poly(glucuronic acid) film comprising the steps of: contacting cellulose with NaOH and a poly(alkylene glycol) to form a solution comprising poly(alkylene glycol), NaOH, and cellulose; contacting the solution comprising poly(alkylene glycol) and cellulose with 2,2,6,6-tetramethylpiperidine-1-oxyl radical and an oxidizing agent to form a solution comprising poly(glucuronic acid) and poly(alkylene glycol); isolating poly(glucuronic acid) from the solution comprising poly(alkylene glycol), 2,2,6,6-tetramethylpiperidine-1-oxyl radical, oxidizing agent, cellulose, and poly(alkylene glycol); contacting poly(glucuronic acid) with an acidic solution of chitosan to form a solution comprising chitosan and poly(glucuronic acid); casting or coating said solution comprising chitosan and poly(glucuronic acid) into a film; and heating the film to crosslink the poly(glucuronic acid) with the chitosan to obtain a chitosan-poly(glucuronic acid) film.

3. 1. A method for making a poly(alkylene glycol)-chitin-poly(glucuronic acid) film comprising the steps of: contacting cellulose with NaOH and a poly(alkylene glycol) to form a solution comprising poly(alkylene glycol), NaOH, and cellulose; contacting the solution comprising poly(alkylene glycol) and cellulose with 2,2,6,6-tetramethylpiperidine-1-oxyl radical and an oxidizing agent to form a solution comprising poly(glucuronic acid) and poly(alkylene glycol); separating the 2,2,6,6-tetramethylpiperidine-1-oxyl radical, the oxidizing agent, and the cellulose from said solution containing poly(glucuronic acid) and poly(alkylene glycol); contacting the solution containing poly(glucuronic acid) and poly(alkylene glycol) with an acidic solution of chitin to form a solution containing chitin, poly(glucuronic acid), and poly(alkylene glycol); casting or coating said solution comprising chitin, poly(glucuronic acid), and poly(alkylene glycol) into a film; and heating the film to crosslink the poly(glucuronic acid) with the chitin to obtain a poly(alkylene glycol)-chitin-poly(glucuronic acid) film.

4. 1. A method for making a chitin-poly(glucuronic acid) film, comprising the steps of: contacting cellulose with NaOH and a poly(alkylene glycol) to form a solution comprising poly(alkylene glycol), NaOH, and cellulose; contacting the solution comprising poly(alkylene glycol) and cellulose with 2,2,6,6-tetramethylpiperidine-1-oxyl radical and an oxidizing agent to form a solution comprising poly(glucuronic acid) and poly(alkylene glycol); isolating poly(glucuronic acid) from the solution comprising poly(alkylene glycol), 2,2,6,6-tetramethylpiperidine-1-oxyl radical, oxidizing agent, cellulose, and poly(alkylene glycol); contacting poly(glucuronic acid) with an acidic solution of chitin to form a solution comprising chitin and poly(glucuronic acid); casting or coating said solution comprising chitin and poly(glucuronic acid) into a film; and heating the film to crosslink the poly(glucuronic acid) with the chitin to obtain a chitin-poly(glucuronic acid) film.

5. 5. The method of any one of claims 1 to 4, wherein the solution comprising poly(alkylene glycol) and cellulose is frozen and then thawed before being contacted with 2,2,6,6-tetramethylpiperidine-1-oxyl radical and the oxidizing agent.

6. 5. The method according to any one of claims 1 to 4, wherein the oxidizing agent is 2,2,5,5-tetramethylpyrroline-N-oxyl, 4,4-dimethyloxazolidine-N-oxyl, sodium hypochlorite, nitrogen dioxide and periodate, metaperiodate and dichromate, or dichromate in oxalic acid.

7. 4. The method of claim 1 or 3, wherein the 2,2,6,6-tetramethylpiperidine-1-oxyl radical, oxidizing agent, and cellulose are separated from the solution containing poly(glucuronic acid) and poly(alkylene glycol) by dialysis against water.

8. The method according to any one of claims 1 to 4, wherein the acidic solution of chitosan or chitin has a pH of 2 to 4.

9. The method of any one of claims 1 to 4, wherein the poly(alkylene glycol) is poly(ethylene glycol).

10. The method of claim 1, wherein the solution containing poly(glucuronic acid) and poly(alkylene glycol) is mixed with a precipitating agent, thereby precipitating the poly(glucuronic acid).

11. The method of any one of claims 1 to 4, wherein the film is heated to 70 to 200°C.

Citation Information

Patent Citations

  • Method for producing composite molded product

    JP2011099107A

  • Granule manufacturing method

    JP2013510920A

  • Cellulose nano-fiber dispersion, method for producing same, modified form of cellulose fiber, and cellulose nano-fiber composite body

    WO2013077354A1